2009
DOI: 10.3174/ajnr.a1593
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Assessment of Intratumoral Susceptibility Signals Using Non-Contrast-Enhanced High-Field High-Resolution Susceptibility-Weighted Imaging in Patients with Gliomas: Comparison with MR Perfusion Imaging

Abstract: BACKGROUND AND PURPOSE:It has been reported that high-resolution susceptibility-weighted imaging (HR-SWI) may demonstrate brain tumor vascularity. We determined whether the degree of intratumoral susceptibility signal intensity (ITSS) on HR-SWI correlates with maximum relative cerebral blood volume (rCBVmax) and to compare its diagnostic accuracy for glioma grading with that of dynamic susceptibility contrast (DSC) perfusion MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
139
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(153 citation statements)
references
References 15 publications
8
139
2
4
Order By: Relevance
“…SWI is a flow compensated high-resolution 3D gradient echo sequence by which the use of phase and magnitude information is able to show tissue with high susceptibility, for example blood deposition products or venous vessels [9, 10]. Its diagnostic use in the field of neuro-oncology is based on the representation of irregularly configured hypointensities inside the tumour, 'Intratumoural Susceptibility Signals' (ITSS) [11,12]. In principle, ITSS can be caused by calcification or deoxyhaemoglobin from microscopic bleeding or venous vessels.…”
Section: Susceptibility-weighted Imaging (Swi)mentioning
confidence: 99%
“…SWI is a flow compensated high-resolution 3D gradient echo sequence by which the use of phase and magnitude information is able to show tissue with high susceptibility, for example blood deposition products or venous vessels [9, 10]. Its diagnostic use in the field of neuro-oncology is based on the representation of irregularly configured hypointensities inside the tumour, 'Intratumoural Susceptibility Signals' (ITSS) [11,12]. In principle, ITSS can be caused by calcification or deoxyhaemoglobin from microscopic bleeding or venous vessels.…”
Section: Susceptibility-weighted Imaging (Swi)mentioning
confidence: 99%
“…Ihr diagnostischer Nutzen im Bereich der Neuroonkologie beruht auf der Darstellung unregelmäßig konfigurierter Hypointensitäten innerhalb des Tumors, sog. "intratumoralen Suszeptibilitätssig-nalen" (ITSS; [44,45]). Prinzipiell kön-nen die ITSS durch Verkalkungen oder Desoxyhämoglobin aus Mikroblutungen oder venösen Gefäßen verursacht werden.…”
Section: Suszeptibilitäts-gewichtete Bildgebungunclassified
“…MR perfusion imaging can also be used to identify with tumor recurrence or focal necrotic after treatment and evaluate prognosis or monitor the efficacy of treatment. Furthermore, numerous studies (Park et al, 2009;Schramm et al, 2010;Ludemann et al, 2009;Park et al, 2009) have shown that perfusion imaging have special superiority in noninvasively grading tumor histology preoperatively. Low-grade astrocytomas are hypoperfused as compared to grade III and IV lesions ( Figure 6-3).…”
Section: Applications Of Perfusion Imagingmentioning
confidence: 99%